Pengaruh Pemberian Abu Sekam Padi terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) - Fatimasara Fatimasara; Fandi Ahmad; Rian Christian Sondakh (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2026)
This study was motivated by the potential use of rice husk ash as an eco-friendly alternative nutrient source to improve the growth of leafy vegetables, particularly mustard greens (Brassica juncea L.). The research aimed to determine the effect of different doses of rice husk ash on the growth and yield of mustard greens. The experiment was conducted from April to July 2025 at the Experimental Garden, Faculty of Agriculture, Madako University Tolitoli, using a Randomized Block Design (RBD) with one factor and five treatment levels: no ash (P0), 250 g/polybag (P1), 375 g/polybag (P2), 500 g/polybag (P3), and 750 g/polybag (P4), each replicated four times. The observed parameters included plant height, number of leaves, and fresh weight. The results showed that rice husk ash application significantly affected the growth and yield of mustard greens. The best performance was observed in the 500 g/polybag treatment (P3), which produced the highest plant height, number of leaves, and fresh weight. In contrast, the 375 g/polybag (P2) and 750 g/polybag (P4) treatments tended to reduce plant growth. It can be concluded that applying rice husk ash at a dose of 500 g/polybag is the optimum level to enhance the growth and yield of mustard greens.